Assessment of miRNAs as transcriptional regulators in respiratory syncytial virus infection through computational analysis and molecular docking studies - Mubashir Hassan; Muhammad Shahzad Iqbal; Muhammad Yasir; Wanjoo Chun; Zainab Yaseen; Saba Shahzadi; Mark E. Peeples; Andrzej Kloczkowski (PLoS ONE, 2026)
Globally, RSV is a major contributor to severe lower respiratory tract infections among children. Despite the significant medical concern posed by RSV, efforts to develop effective vaccines and antiviral drugs have largely fallen short, with the exception of immune prophylaxis available only for specific high-risk infants. We employed a suite of computational tools to investigate the role of microRNAs in the host’s response to RSV infection. miRanda and RNAHybrid were instrumental in predicting microRNA-mRNA binding sites. For a deeper structural analysis, MC-Fold and MC-Sym were used to predict the 3D structures of both the miRNAs and their target mRNAs. The interactions between these molecules were then studied through RNA-RNA docking, with the resulting poses evaluated based on binding affinities and interaction profiles. This analysis focused on twelve selected miRNAs and their binding to specific sites on RSV mRNA. Finally, molecular dynamics (MD) simulations were conducted to evaluate the stability of the docked complexes. Taken together, these results suggest that two miRNAs, hsa_miR-2278 and hsa_miR-6732-3p, could potentially regulate the transcriptional activity during RSV infection and may warrant consideration as therapeutic agents.